Effects of light-load maximal lifting velocity weight training vs. combined weight training and plyometrics on sprint, vertical jump and strength performance in adult soccer players - Rodriguez-Rosell, D.; Torres-Torrelo, J.; Franco-Márquez, F.; González-Suárez, J. M.; González-Badillo, J. J. (Journal of Science and Medicine in Sport, 2017)
Objectives: The purpose of this study was to compare the effects of combined light-load maximal lifting velocity weight training (WT) and plyometric training (PT) with WT alone on strength, jump and sprint performance in semiprofessional soccer players. Design: Experimental, pre-post tests measures. Methods: Thirty adult soccer players were randomly assigned into three groups: WT alone (FSG, n = 10), WT combined to jump and sprint exercises (COM, n = 10) and control group (CG, n = 10). WT consisted of full squat with low load (~45-60% 1RM) and low volume (4-6 repetitions). Training program was performed twice a week for 6 weeks of competitive season in addition to 4 soccer sessions a week. Sprint time in 10 and 20 m, jump height (CMJ), estimated one-repetition maximum (1RMest) and velocity developed against different absolute loads in full squat were measured before and after training period. Results: Both experimental groups showed significant improvements in 1RMest (17.4-13.4%; p < 0.001), CMJ (7.1-5.2%; p < 0.001), sprint time (3.6-0.7%; p < 0.05-0.001) and force-velocity relationships (16.9-6.1%; p < 0.05-0.001), whereas no significant gains were found in CG. No significant differences were found between FSG and COM. Conclusions: Despite FSG resulted of greater increases in strength variables than COM, this may not translate into superior improvements in the sport-related performance. In fact, COM showed higher efficacy of transfer of strength gains to sprint ability. Therefore, these findings suggest that a combined WT and PT program could represent a more efficient method for improving activities which involve acceleration, deceleration and jumps compared to WT alone.